Precedence: Social Differentiation in the Austronesian World - P. Vischer, Michael (ANU Press, 2009)
This collection of papers is the sixth volume in the Comparative Austronesian series. The papers that comprise this volume examine the concept of precedence as a form of local discourse and as a mechanism for ordering status, at different levels, within specific Austronesian-speaking societies. This is the first volume of its kind to focus entirely on precedence and to provide an explication of its social uses and the way in which it is contested. Each paper is ethnographically-focused and offers its own distinctive approach to the examination of precedence. The papers, however, relate closely to one another and are thus able to proffer a variety of comparative reflections.